ALMA Deep Field in the SSA22 proto-cluster at z = 3. Issue Volume 15:Issue S352(2019) (June 2019) - Umehata, Hideki
Abstract: Galaxies and nuclei in dense environment at high redshift provide a good laboratory to investigate accelerated, most extreme evolution of galaxies. The SSA22 proto-cluster at z = 3.1 is known to have a three-dimensional 50 (comoving) Mpc-scale filamentary structure, traced by Lyα emitters, which makes the field a suitable target in this regard. To identify dust-obscured star-formation, a contiguous 20 arcmin 2 region at the node of the cosmic structure was observed in ALMA band 6. In total 57 ALMA sources have been identified above 5 σ, which makes the field one of the richest field in ALMA-identified (sub)millimeter galaxies. The follow-up spectroscopy confirmed about 20 sources as exact proto-cluster members so far. Together with high X-ray AGN fraction, our results suggest that the vigorous star formation activity and the growth of super massive black holes occurred simultaneously in the densest regions at z ∼ 3.